Influence of Psychological Factors in Breast and Lung Cancer Risk – A Systematic Review - Pereira, Maria Angelina; Araújo, António; Simões, Mário; Costa, Catarina (Frontiers in Psychology, 2022)
Introduction: In 2020, according to the Global Cancer Observatory, nearly 10 million people died of cancer. Amongst all cancers, breast cancer had the highest number of new cases and lung cancer had the highest number of deaths. Even though the literatures suggest a possible connection between psychological factors and cancer risk, their association throughout studies remains inconclusive. The present systematic review studied the connection between psychological factors and the risk of breast and lung cancer, prior to a cancer diagnosis. The psychological factors of trauma, grief, and depression were studied. Methods: The current systematic review was carried out across multiple databases in two phases, an initial exploratory research in June 2020, refined with a second electronic research in December 2020. The inclusion criteria included studies describing the association between trauma, PTSD, grief, and depression with breast and lung cancer risk. The psychological data collection must have been carried out prior to a confirmed breast or lung cancer diagnosis, and accessed through self-report measures, questionnaires, clinical interviews, or clinical diagnoses. Study reports had to contain information about the incidence of cancer and effect size. The exclusion criteria were studies in which psychological factors were collected after cancer diagnosis. Results and Conclusions: A total of 26 studies were included. Although non-consensual, the findings from the present systematic review suggest that, in addition to the known risk factors, psychological factors may play an important role in the aetiology of both breast and lung cancer. To include psychological factors as a variable that affects cancer development may be fundamental to opening new avenues for prevention and intervention.